EPID-07. Outcome disparities in children, adolescents and young adults with medulloblastoma: A population-based analysis. (3rd June 2022) - Genecin, Isabel; Fullwood, Dottington; Moisander-Joyce, Hanna; Padilla, Oscar; Minns, Hanna; Garvin, James; Szalontay, Luca; Wu, Cheng-Chia; Kahn, Justine; Gartrell, Robyn D
Abstract: Medulloblastoma (MB) is the most common high-grade primary pediatric brain tumor. Recent registry-based studies in children with central nervous system (CNS) tumors have demonstrated that survival outcomes differ by race/ethnicity in multivariable analyses, with Hispanic patients having highest hazard of death overall. To investigate this finding in MB patients, we examined survival in children (0-14 years) and adolescent/young adults (15-39 years) with MB from 2007-2016 in the 2018 Surveillance Epidemiology and End Results Program database, using Kaplan Meier analysis, log-rank test and Cox proportional hazard ratios (HR) with 95% confidence intervals (CI). Race and ethnicity were categorized according to the U.S. Census, with Hispanic ethnicity (yes/no) analyzed separately from race (Black, White, Asian, Other). Among 1612 patients, 81% were White, 9% were Black, 8% were Asian or Pacific Islander, and 2% were from "other" or unknown racial groups. 28% of the cohort was of Hispanic ethnicity. Univariate analysis found that Black patients had a significantly higher hazard of death than White patients (HR=1.55, CI: 1.16 – 2.08, p=0.003). In contrast, Hispanic ethnicity was not significantly associated with outcome (HR=0.98, CI: 0.79-1.21, p=0.8). Medicaid or no insurance (vs. private) were each significantly associated with higher risk of death; Medicaid (HR =1.23, CI = 1.01 - 1.51, p=0.041); Uninsured (HR=2.07, CI=1.41-3.02, p=<0.001). Of the treatment modalities analyzed, patients who received neither chemotherapy nor radiation experienced higher hazard of death than patients who received both treatments (HR=3.63, CI 2.78-4.76, p=<0.001). Consistent with observations in other cancers, racial disparities are observed in patients with MB, with Black race conferring increased risk of death. Public insurance was also significantly associated with death, as was not receiving combined-modality therapy. Further work is needed to understand the multilevel factors impacting diagnosis, treatment and outcome among children and AYAs with MB and prospective studies are warranted.